Measuring how changes in code readability attributes affect code quality evaluation by Large Language Models - Simões, Igor Regis da Silva; Venson, Elaine (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
Code readability is one of the main aspects of code quality, influenced by various properties like identifier names, comments, code structure, and adherence to standards. However, measuring this attribute poses challenges in both industry and academia. While static analysis tools assess attributes such as code smells and comment percentage, code reviews introduce an element of subjectivity. This paper explores using Large Language Models (LLMs) to evaluate code quality attributes related to its readability in a standardized, reproducible, and consistent manner. We conducted a quasi-experiment study to measure the effects of code changes on Large Language Model (LLM)s’ interpretation regarding its readability quality attribute. Nine LLMs were tested, undergoing three interventions: removing comments, replacing identifier names with obscure names, and refactoring to remove code smells. Each intervention involved 10 batch analyses per LLM, collecting data on response variability. We compared the results with a known reference model and tool. The results showed that all LLMs were sensitive to the interventions, with agreement with the reference classifier being high for the original and refactored code scenarios. However, this agreement diverged for the other two interventions. The LLMs demonstrated a strong semantic sensitivity that the reference model did not fully capture. A thematic analysis of the LLMs’ reasoning confirmed their evaluations directly reflected the nature of each intervention. The models also exhibited response variability, with 9.37% to 14.58% of executions showing a standard deviation greater than zero, indicating response oscillation, though this did not always compromise the statistical significance of the results. LLMs demonstrated potential for evaluating semantic quality aspects, such as coherence between identifier names, comments, and documentation with code purpose. Further research is needed to compare these evaluations with human assessments and explore real-world application limitations, including cost factors.